Employee Performance Model based on Knowledge Management and Employee Retention - Saiyid Syech; Anisah Anisah; Amilia Paramita Sari (J-MAS (Jurnal Manajemen dan Sains), 2022)
The aims of this study are to analysis the influence of knowledge management on employee retention and the effect of both on employee performance. The sample in this study is 173 employees who work in finance companies in Jambi City, the data used are primary data derived from questionnaires, processed and analyzed using structural equation modeling. The results of the study prove that there is a positive and significant effect of knowledge management on employee retention and there is a positive effect of both on employee performance.